Trend of hospitalizations for ambulatory care sensitive conditions and related aspects in Sergipe, 2010 to 2019 - Rynat Dasaev Oliveira Chagas; Joao Batista Cavalcante Filho; Marco Antônio Prado Nunes (Hospital de Clínicas de Itajubá, 2022)
Objective: To analyze the trend of hospitalization rates for ambulatory care-sensitive conditions (HACSC) in Sergipe and its seven health regions between 2010 and 2019, correlating with financial investments in health and primary care, strategy coverage of family health, and the number of hospital beds. Methods: This is an ecological time-series study trend with secondary data from the Ministry of Health. The trend verification was done by segmented linear analysis and the correlation between the variables by Spearman's correlation. Results: HACSC in the state of Sergipe showed a trend towards stability. In the Nossa Senhora do Socorro region, an increasing rate trend was identified from 2010 to 2017 and a non-significant decreasing trend from 2017 to 2019, with a negative correlation with per capita investment in PHC. The Itabaiana region showed a trend of reduction in rates from 2010 to 2012, followed by a trend of growth in rates from 2012 to 2020, with no significant correlation with any of the variables. Conclusions: Monitoring HACSC rates and understanding their multifactorial influence are essential since this indicator is helpful in local situational diagnosis and contributes to planning actions.